Early Cretaceous Extensional‐tectonism‐related petrology of the Gan‐Hang Belt SE China: Lingshan A‐type granite at ca. 130 Ma. (22nd December 2017) - Wang, Cunzhi; Zhao, Xilin; Huang, Zhizhong; Xing, Guangfu; Wang, Lianxun
Abstract : A number of Late Mesozoic (ca. 130 Ma) A‐type granitic plutons have been identified in Southeast (SE) China. The Lingshan pluton, located in the Gan‐Hang Belt, is a typical one which is mainly composed of coarse‐grained biotite monzogranite in the pluton centre and medium‐ to coarse‐grained syenogranite on the margin. Zircons from three representative samples show U–Pb ages of 132.0 ± 1.3, 134.4 ± 2.1, and 133.0 ± 1.9 Ma, respectively, indicating that the Lingshan pluton were formed in the Early Cretaceous. The Lingshan granites display typical A‐type affinities, with high SiO2, K2 O, Na2 O + K2 O, rare earth element (REE) and high field strength element (HFSE) contents, high Ga/Al and Fe # [FeO T /(FeO T  + MgO)] ratios and Zr + Nb + Ce + Y contents, and apparent depletion of Ba, Sr, Ti, and Eu. The calculated zircon saturation temperatures (TZr ) are high, ranging from 841 to 966 °C (mean of 886 °C). The εHf (t) values and TDM2 (Hf) of the Lingshan granites mainly vary from −3.0 to 0.2 and 1.18 to 1.38 Ga, respectively. Consistently, the εNd (t) values vary from −3.9 to −2.8 and TDM2 (Nd) range from 1.16 to 1.26 Ga. These isotopic data indicate that the Lingshan granites were likely to be generated by partial melting of Mesoproterozoic metamorphic basement rocks with the involvement of a certain amount of mantle‐derived materials. Subsequent fractional crystallization processes were also suggested during subsequent magma evolution. We propose that the ca. 130 Ma Lingshan granites together with other coetaneous A‐type granitic rocks from adjacent region indicate a back‐arc extensional setting in SE China during Early Cretaceous. The extension event might be caused by the rollback of paleo‐Pacific Plate which results in upwelling of the asthenosphere and subsequently induces a high degree partial melting of Mesoproterozoic basement sedimentary material, to generate the A‐type granitic plutons along the Gan‐Hang Belt.